'Not dead … abandoned' – a clinical case study of childhood and combat-related trauma. Issue 1 (2nd January 2017) - Challenor, Julianna
Abstract: This clinical case study examines inter-subjective processes with a counselling client who presented with symptoms of complex trauma including severe anxiety, low mood, dissociation and suicidality. Therapy lasted 12 months and was ended abruptly by the client. Psychoanalytic and phenomenological hermeneutic frameworks are drawn on in theorizing the work. From this perspective, loss associated with trauma is conceptualized as relational, as traumatic states threaten psychological organization and the continuing experience of relational ties that are needed for survival. Dissociation is understood as a defensive state that changes the way that temporality is experienced. The client's capacity for dissociation appeared to have developed in early childhood in response to physical abuse, predisposing him to further ongoing and severe trauma as an adult soldier. There will be a focus on the way that dissociation and enactment in the therapeutic relationship limited the therapist's capacity to provide the client with inter-subjective regulation of disavowed affect. The client's unconscious experience of unbearable affect led to a breakdown of the therapeutic relationship and termination of therapy. Using detailed session and supervision notes and correspondence received from the client, theory and practice links will be evaluated, as well as some methodological aspects of case study research.